HUBUNGAN STIKERISASI PROGRAM PERENCANAAN PERSALINAN DAN PENCEGAHAN KOMPLIKASI DENGAN PENANGANAN KOMPLIKASI - Nursiyam, Nursiyam (JURNAL MEDIA KESEHATAN, 2014)
The direct causes of maternal mortality in Indonesia is bleeding (32%), postpartum hemorrhage, eclampsia (13%), unsafe abortion (11%), infection (10%) and obstructed labor (9%). P4K with stickers is a breakthrough in reducing maternal mortality and newborn. The high incidence of obstetric complications in the District of Talbot District Seluma. The purpose of the study to determine the relationship stikerisasi P4K with handling complications in postpartum mothers. The study design was a descriptive, cross-sectional design. Data obtained from secondary data sheet checklist. The samples were puerperal women who experience complications. Sampling with a total sampling technique. The results showed 81.4% had 87.3% stikerisasi P4K and already getting treatment complications. The results showed no relationship between stikerisasi P4K with handling complications (p = 0,000 < ,005 and OR = 55,688). Expected midwife as further improve performance by IEC on P4K.